La quatrième vague du féminisme : quel impact sur le champ littéraire ? - Mairesse, Lise (Université catholique de Louvain, 2022)
Ce mémoire a pour but d'examiner l'éventuel impact qu'a eu la quatrième vague du féminisme sur la situation des femmes dans le champ littéraire. Dans sa première partie de contextualisation, il trace les contours d'une histoire littéraire au féminin marquée par l'invisibilisation, l'exclusion et la marginalisation. Dans sa seconde partie, il fait état d'une série de transformations ayant récemment agité le monde de l'édition depuis la déferlante #MeToo, la plus notable étant l'essor inédit pris par l'édition d'ouvrages de non-fiction féministes, une pratique qui témoigne tantôt de l'engagement profond d'une série de nouvelles maisons d'édition indépendantes, tantôt de la pratique du "feminism washing" par les grandes maisons généralistes. La troisième et ultime partie vise à répondre à la question suivante : les inégalités de genre, de quelque nature qu'elles soient, affectent-elles autant le champ littéraire depuis #MeToo? Y seront abordées les questions du plafond de verre, des inégalités salariales, du capital symbolique accordé aux autrices et du harcèlement sexuel au sein du milieu littéraire.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; discipline; intersectionnalité; inégalités; metoo; mémoires/thèses; patriarcat; prix littéraires; périodes historiques; ressource en ligne; sciences humaines; sociologie; sofia; systèmes d'oppression; thématiques; travail; violences; violences sexistes et sexuelles; écriture des femmes*; études littéraires

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)
Organisé par l’Observatoire interdisciplinaire de création et de recherche en musique et le Centre des musiciens du monde, le colloque Femmes musiciennes du monde visait à explorer les parcours professionnels de musiciennes migrantes. Des conférences et tables rondes ont fait intervenir des chercheuses en sociologie, anthropologie, musicologie et ethnomusicologie ainsi que des musiciennes ayant immigré à Montréal. De la combinaison de ces savoirs scientifique et expérientiel s’est dégagée une série de difficultés et défis récurrents pour les femmes en musique : invisibilisation du travail, différenciations et discriminations genrées dans un milieu majoritairement masculin, enjeux liés au corps féminin ainsi qu’à la mobilité géographique. Or, il s’est aussi affirmé des spécificités d’expériences, de profils et de stratégies selon les parcours migratoires. Cette note de terrain synthétise les principaux constats, mais aussi les limites des discussions de ce colloque avant d’identifier quelques-uns des nombreux efforts qu’il reste à déployer pour mieux comprendre les réalités de telles artistes.
https://id.erudit.org/iderudit/1090520ar
Keywords: 2000 à aujourd'hui; 2020-2029; agentivité; anthropologie; approches et analyses; arts; corps; discipline; discrimination; femmes* artistes; femmes* immigrantes; femmes* musiciennes; intersectionnalité; invisibilité historique; musique; périodes historiques; racisme; ressource en ligne; savoir expérientiel; sciences humaines; sexisme; sociologie; systèmes d'oppression; thématiques; travail; travail invisible; violences

Social vulnerability and the impact of policy responses to COVID‐19 on disabled people - Mladenov, Teodor; Brennan, Ciara Siobhan (Sociology of Health & Illness, 2021)
In this paper, we propose a conceptual framework for understanding the impact of the policy responses to COVID-19 on disabled people. These responses have overwhelmingly focused on individual vulnerability, which has been used as a justification for removing or restricting rights. This suggests the need to shift the attention towards the social determinants of disabled people's vulnerability. We do this by bringing literature on social vulnerability in disaster risk management or 'disaster studies' in contact with key concepts in disability studies such as the social model of disability, independent living, intersectionality, and biopower. Empirically, we draw on the findings of the global COVID-19 Disability Rights Monitor (www.covid-drm.org), as well as on reports from academic journals, civil society publications, and internet blogs. We put the proposed conceptual framework to work by developing a critical analysis of COVID-19 policies in three interrelated areas-institutional treatment and confinement of disabled people, intersectional harms, and access to health care. Our conclusion links this analysis with strategies to address disabled people's social vulnerability in post-pandemic reconstruction efforts. We make a case for policies that address the social, economic, and environmental conditions that disproportionately expose disabled people to natural disasters and hazards.
https://www.ncbi.nlm.nih.gov/pmc/articles/PMC8652534/
Keywords: approches et analyses; capacitisme; corps; covid-19; discipline; intersectionnalité; ressource en ligne; santé; sciences humaines; sociologie; soins de santé; thématiques; vulnérabilité

Gendered care work and environmental injustice: A feminist analysis of educator's emotional labor in disaster recovery - Shtob, Daniel A.; Petrucci, Larissa (Environmental Justice, 2021)
Although environmental justice researchers have long been interested in the connections between disaster recovery, gender, and home- and community-based care, the consequences of the post-disaster performance of emotional labor by workers in care occupations have largely gone unnoticed. To address this gap in the environmental injustice literature, in this exploratory article we employ a feminist analysis of firsthand accounts of elementary educators' professional and personal experiences caring for their students in the Florida Keys after Hurricane Irma. We find that caring labor was increasingly necessary in the post-disaster context, both inside and outside the classroom. Teachers and other care professionals in feminized occupations may, therefore, perform an emotional double duty, supporting their students' emotional needs while also contending—as working- and middle-class individuals—with the personal consequences of disaster. We suggest that these educators may bear an unrecognized and undercompensated disproportionate burden at the intersection of class and occupational status. Because of this, we introduce an underexplored component to the racialized disaster patriarchy and intersectional disaster research: feminized occupational status. Inspired by environmental justice research legacies developed in the wake of earlier Gulf Coast disasters, we draw attention to the contributions of these absolutely essential recovery workers and how they may experience environmental injustice even as they contribute to others' recovery. Our goals are to promote recognition and fair distribution of burdens, encourage research into the contours of environmental justice and care work, and support the development of more just planning, training, and compensation regimes.
Keywords: amériques; approches et analyses; care; discipline; floride; intersectionnalité; patriarcat; régions géographiques; sciences humaines; sociologie; systèmes d'oppression; thématiques; travail; émotions

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'État; violences gynécologiques et obstétricales; états-unis